EFFORTS TO RESILIENCE THE FAMILY'S ECONOMY DURING THE PANDEMIC AND POST-COVID-19 IN SUKATANI VILLAGE, WANASALAM DISTRICT, LEBAK REGENCY: UPAYA KETAHANAN EKONOMI KELUARGA SAAT PANDEMI DAN PASCA COVID-19 DI DESA SUKATANI KECAMATAN WANASALAM KABUPATEN LEBAK - M. Figo Abdi Ragyl; Khaeruman Khaeruman; Rozzan Fauza; Dini Puspita; Dendi Wira Permana; Fitri Cipta Noviani; Irma Nurhadiati; Sopiyana Sopiyana; Muhammad Ilhamullah; Rio Pratama Oktadila (Yayasan Education and Social Center, 2022)
Covid-19 cripples the economy, the impact can reduce income which affects the family's economic capacity to survive during the Covid-19 pandemic. Now is the time to live after Covid-19, but the impact it has does not mean that it no longer exists, but only diminishes. Currently, the government is in the process of observing information that there is currently a new virus, caution is required for certain restrictions. The economic resilience of families after Covid-19 has declined, particularly in terms of income and capacity to meet family needs. But from the aspect of residential property, financing for children's education and family financial security, the economic resilience of the family can be considered quite good. However, the recommendations are quite good for family financial management strategies. The method of implementing community service activities consists of three stages. First, the preparatory phase includes initial observations. The second step is the implementation of the program in the form of discussions. The third step is the evaluation step. Evaluation is done by comparing the condition of the family before and after the implementation of the program with interviews and observation methods. Based on indicators of residential property, family income, financing for children's education and family financial security, it was found that the economic resilience of families in Sukatani Village in the post-Covid-19 era in terms of income and ability to meet family needs